Influence of mining activities on hydrological processes in the mining district, Loess Plateau: insights from spatio-temporal variations of δD and δ18O - Zhang, Wenrui; Zhang, Junyi; Yang, Nuan; Duan, Limin (Frontiers in Environmental Science, 2024)
Under the influence of mining activities, investigating hydrological processes is an important cornerstone of water resources and eco-environment protection. In this study, the spatio-temporal variations of stables isotopic compositions (δD and δ18O) of river water and groundwater in five periods of a hydrological year were analyzed to identify the origin and hydraulic connection of water bodies in the mining district under mining disturbance. The δD and δ18O indicate that the water bodies in the study area is mainly recharged by local precipitation and undergo evaporation. There is a close hydraulic connection between river water, mine water and groundwater, the deep confined water is affected by the river water and phreatic water due to the developing water-conducting fractures. The δ18O of phreatic water in each period is depleted in southwest and enriched in northeast of the study area. The δ18O of confined water has an obvious spatial variation in the wet season due to the combined effects of the opencast working and underground mining, and a uniform spatial variation in the dry season. Compared with dry season, mining disturbance has greater impact on river water and groundwater in wet season. The difference in spatial variation of δ18O between phreatic and confined water may attribute to the easier recovery of phreatic water than confined water after mining disturbance. This finding provides important information about hydrological characteristics of Pingshuo mining district.